Modern particle physics - Thomson, Mark. (New Delhi: Cambridge University Press, 2019)
"Unique in its coverage of all aspects of modern particle physics, this textbook provides a clear connection between the theory and recent experimental results, including the discovery of the Higgs boson at CERN. It provides a comprehensive and self-contained description of the Standard Model of particle physics suitable for upper-level undergraduate students and graduate students studying experimental particle physics. Physical theory is introduced in a straightforward manner with full mathematical derivations throughout. Fully-worked examples enable students to link the mathematical theory to results from modern particle physics experiments. End-of-chapter exercises, graded by difficulty, provide students with a deeper understanding of the subject. Online resources available at www.cambridge.org/MPP feature password-protected fully-worked solutions to problems for instructors, numerical solutions and hints to the problems for students and PowerPoint slides and JPEGs of figures from the book"--
Machine generated contents note: 1. Introduction; 2. Underlying concepts; 3. Decay rates and cross sections; 4. The Dirac equation; 5. Interaction by particle exchange; 6. Electron-positron annihilation; 7. Electron-proton elastic scattering; 8. Deep inelastic scattering; 9. Symmetries and the quark model; 10. Quantum chromodynamics; 11. The weak interaction; 12. The weak interactions of leptons; 13. Neutrinos and neutrino oscillations; 14. CP violation and weak hadronic interactions; 15. Electroweak unification; 16. Tests of the Standard Model; 17. The Higgs boson; 18. The Standard Model and beyond; Appendixes; References; Further reading; Index.
Includes bibliographical references (page 545) and index.
Keywords: Particles (Nuclear physics) -- Textbooks; SCIENCE / Nuclear Physics